HER2 STATUS BREAST CANCER IN A POPULATION OF WESTERN ALGERIA: Life Science-Oncology - ZOHRA, BEKKOUCHE; YOUCEF, GUEDDOUAR; CHAHINAIZE, ZAOUI; FATIMA ZOHRA, EL KEBIR (International Journal of Life Science and Pharma Research, 2013)
The HER2 gene is an oncogene encoding a human growth factor and amplified in breast cancer. Overexpression of the corresponding protein is usually the result of HER2 gene amplification secondary to oncogenic transformation. The determination of HER2 status by immunohistochemistry (IHC) allows visualization of the protein in situ: assessment and quantification of the overexpression of HER2 to target HER2 + eligible for specific therapeutic (Trastuzumab or Herceptin ®). The assessment of HER2 status is performed in correlation with clinical features, histopathological and biological mammary tumors. Material and methods: Our study from June 2007 to June 2011, 677 patients with interested invasive cancers. We used IHC method for assessing HER2 overexpression, performed on tissue blocks fixed in neutral buffered formol with the polyclonal specific antibody A 485 (Dako). Results: Age lies between 23 & 81 years old (mean age 45 ± 3 .45), histologic type is found most invasive ductal carcinoma (88%), the size pT2 (56%), grade III SBR (68% ), nodal status pN + (56%), co-expression of hormone receptors ER + PR + (16%), ER + PR-(12%) RE-RP- (67%), ER-PR + (05%) . HER2 status: membrane labeling, score 0-1 + (61%), score 3 + (34%), score 2 + (05%). Conclusion:HER2 + tumors are found associated with a proportionally high SBR grade, pT 3 and ER-PR-. HER2 status does not appear to be associated with the histological type, pN or age of patients. The HER2 gene is an oncogene encoding a human growth factor and amplified in breast cancer. Overexpression of the protein is corresponding usually the result of HER2 gene amplification secondary to oncogenic transformation.